2019
DOI: 10.21034/iwp.17
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimal Paternalistic Savings Policies

Abstract: We study optimal savings policies when there is a dual concern about undersaving for retirement and income inequality. Agents differ in present bias and earnings ability, both unobservable to a planner with paternalistic and redistributive motives. We characterize the solution to this two-dimensional screening problem and provide a decentralization using realistic policy instruments: mandatory savings at low incomes but a choice between subsidized savings vehicles at high incomes-resembling Social Security, 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…More recently, Moser and de Souza e Silva (2019) investigate optimal retirement savings policies when there is a paternalistic motive to undo an individual's present bias combined with a redistributive motive. These authors explore the link between savings choices throughout the income distribution, identifying a trade‐off between these two motives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recently, Moser and de Souza e Silva (2019) investigate optimal retirement savings policies when there is a paternalistic motive to undo an individual's present bias combined with a redistributive motive. These authors explore the link between savings choices throughout the income distribution, identifying a trade‐off between these two motives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The key insight from the literature on optimal capital (saving) taxation with a paternalist social planner is that saving should be enhanced if individuals are too impatient or have a self‐control problem (Aronsson & Johansson‐Stenman, 2018; Fadlon & Laibson, 2017; Farhi & Gabaix, 2020; Moser & Olea de Souza e Silva, 2019; Pavoni & Yazici, 2017; Yazici & Pavoni, 2017). This notion implies a negative optimal tax on savings.…”
Section: Interpretations Of Pareto Weightsmentioning
confidence: 99%
“…Although most of our analyses do not specify the sources of intergenerational time‐preference heterogeneity, a plausible interpretation is that children have present bias. In the context of capital taxation with individuals having present bias, studies found that paternalistic policymakers implement a negative marginal capital taxation that enhances savings (e.g., Bishnu & Wang, 2013; Krusell et al, 2010; Moser & Olea de Souza e Silva, 2019; Pavoni & Yazici, 2017). In other words, subsidies for savings improve social welfare by disincentivizing individuals' current consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Since this health state is not static but evolves according to an SIRD model, the tradeoff faced by the government is not static but dynamic and the time inconsistency problem evolves over time. 7 Our analysis of rules for lockdown policy in the presence of noncontractible information relates to a growing literature on commitment versus flexibility in macroeconomics (Athey et al, 2005;Amador et al, 2006;Halac andYared, 2014, 2018;Moser and Olea de Souza e Silva, 2019).…”
Section: Introductionmentioning
confidence: 99%